O relacionamento com o cliente como diferencial competitivo de clínicas veterinárias da cidade de Chapecó-SC - Martins, Gesibel Makoski (2018)
The present research aimed to analyze how Customer Relationship contributes as Competitive Differential to Veterinary Clinics in the city of Chapecó-SC. The research emerged from the questioning of how these companies get to know so deeply the needs of customers and the pets they serve. Three specific objectives were identified: To identify the marketing strategies used by the Veterinary Clinics; Recognize the customer service process; and Diagnose how relationship marketing can contribute as a competitive advantage. This study was characterized as applied and exploratory research. To achieve the objectives there was primary data collection. Three questionnaires were developed and applied: one for managers, one for employees and the other for clients of the Veterinary Clinics. Twelve (12) managers' questionnaires were obtained, 32 (thirty-two) of employees and 100 (one hundred) of clients. Data analysis was performed using descriptive statistics. Through it were made analyzes of frequency and presentation of the data in tables and graphs. The results showed that managers and employees have training in the area and participate in congresses and fairs to follow market trends. It was emphasized that the Veterinary Clinics are betting on the quality of the products and services offered, since the pets are for the clients members of their families. In this sense, it was emphasized that the price is not the most relevant item for the customer. In addition, the highlight was the customer demand and the search for a differentiated service. To meet this market, companies have detailed information about their customers, their purchase histories, preferences and complaints. All records are used to address them. It was observed that the clients, in general, are female with age group of 22 to 29 years, income of R $ 4,000.00 to 6,000.00 monthly, marital status married and without children. Most of them own a pet and go to the clinic once a month or once a week. In relation to the main products offered, the most important were Accessories, Medicines, Food, Hygiene and Perfumery products. The main services offered were Bath and haircut, Aesthetic Services and Clinical Services. For managers, the differential of the companies is the Customer Service followed by the Customer Relationship. Customers for the differential are the Qualified Professionals. It was concluded that the clients pointed out the trained professionals as a differential, due to the Clinical Services that the animals are submitted to. In spite of this, it is considered that the Customer Relationship is essential, since these professionals need to have sensitivity to the customer service, considering the needs of the clients and the pets.